2013
DOI: 10.1371/journal.pone.0064076
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of the Human Myeloma IgG2

Abstract: Human immunoglobulin G, subclass 2 (hIgG2), plays an important role in immunity to bacterial pathogens and in numerous pathological conditions. However, there is a lack of information regarding the three-dimensional (3D) structure of the hIgG2 molecule. We used electron microscopy (EM), differential scanning microcalorimetry (DSC) and fluorescence for structural analysis of the hIgG2. DSC and fluorescence indicated two types of interaction between CH1 domain of Fab (antigen-binding fragment/subunit) and CH2 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
(100 reference statements)
1
14
2
1
Order By: Relevance
“…Detection of these species after disruption of all hinge disulfides indicates the presence of strong noncovalent forces between the HCs, in alignment with the extensive Fab-Fab and Fab-C H 2 interactions previously reported for the B isoform. 26,51 Our observed disulfide isoform conversion directionality is in agreement with previous studies that have reported conversion of the A → A/B → B forms in a reducing environment similar to physiological conditions. 24,25 The higher thermal stability of the IgG2-B mAb and ADCs observed in this study provides further evidence that IgG2 disulfide scrambling favors the thermodynamic product.…”
Section: Discussionsupporting
confidence: 92%
“…Detection of these species after disruption of all hinge disulfides indicates the presence of strong noncovalent forces between the HCs, in alignment with the extensive Fab-Fab and Fab-C H 2 interactions previously reported for the B isoform. 26,51 Our observed disulfide isoform conversion directionality is in agreement with previous studies that have reported conversion of the A → A/B → B forms in a reducing environment similar to physiological conditions. 24,25 The higher thermal stability of the IgG2-B mAb and ADCs observed in this study provides further evidence that IgG2 disulfide scrambling favors the thermodynamic product.…”
Section: Discussionsupporting
confidence: 92%
“…Prior to this study, only a small number of ESTs (307 ESTs) in NCBI were available for this species, thus our data enrich the existing genetic resources. A total of 137 candidate genes were potentially involved in immune responses, a high ratio most likely due to an effective stimulation with ranavirus, since ranavirus infection can induce robust immune response in amphibians (Grayfer et al, 2014;Ryazantsev et al, 2013). It has long been recognized that amphibian thymus is the primary lymphoid organ (Chen and Robert, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, it represents the first hinge-containing IgD in nonmammalian tetrapods, since no hinges have been reported in the lower vertebrate IgD sequenced to date. The hinge region is critical for Ig function: it confers conformational flexibility, thus facilitating antigen binding and triggering effector functions (Ryazantsev et al, 2013). This segment is generally present in mammalian Igs, but it is assumed to be evolved in lower vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Space-filled rendering of murine IgG in Jmol (PDB ID: 1IGY [24]) with the Fab and Fc domains outlined. Mammalian IgG has two long axes (with typical lengths of approximately 10–15 nm[24, 25]) and one short axis with a unique Y- or T-shaped geometry.…”
Section: Figurementioning
confidence: 99%